Transparency and accountability in local government financial reporting: A systematic literature review - Jannah, Miftahul; Haliah, Haliah; Nirwana, Nirwana (Social Sciences Insights Journal, 2025)
This systematic literature review explores the crucial role of transparency and accountability in local government financial reporting. The paper synthesizes various studies examining how digitalization, the adoption of international accounting standards such as IPSAS, and robust governance frameworks contribute to improving financial reporting practices. Through an analysis of existing literature, this review highlights the positive impacts of transparency and accountability in enhancing public trust, improving decision-making, and ensuring the responsible use of public resources. However, challenges such as insufficient capacity, political interference, and the complexity of global standards remain significant obstacles to effective financial reporting. The review emphasizes the need for continuous improvement in local government financial reporting systems to promote greater accountability and foster good governance.